Tissue Transglutaminase Promotes Early Differentiation of Oligodendrocyte Progenitor Cells - Espitia Pinzon, Nathaly; van Mierlo, Hanneke; de Jonge, Jenny C.; Brevé, John J. P.; Bol, John G. J. M.; Drukarch, Benjamin; van Dam, Anne-Marie; Baron, Wia (Frontiers in Cellular Neuroscience, 2019)
Demyelinated lesions of the central nervous system are characteristic for multiple sclerosis (MS). Remyelination is not very effective, particular at later stages of the disease, which results in a chronic neurodegenerative character with worsening of symptoms. Previously, we have shown that the enzyme Tissue Transglutaminase (TG2) is downregulated upon differentiation of oligodendrocyte progenitor cells (OPCs) into myelin-forming oligodendrocytes and that TG2 knock-out mice lag behind in remyelination after cuprizone-induced demyelination. Here, we examined whether astrocytic or oligodendroglial TG2 affects OPCs in a cell-specific manner to modulate their differentiation, and therefore myelination. Our findings indicate that human TG2-expressing astrocytes did not modulate OPC differentiation and myelination. In contrast, persistent TG2 expression upon OPC maturation or exogenously added recombinant TG2 accelerated OPC differentiation and myelin membrane formation. Continuous exposure of recombinant TG2 to OPCs at different consecutive developmental stages, however, decreased OPC differentiation and myelin membrane formation, while it enhanced myelination in dorsal root ganglion neuron-OPC co-cultures. In MS lesions, TG2 is absent in OPCs, while human OPCs show TG2 immunoreactivity during brain development. Exposure to the MS-relevant pro-inflammatory cytokine IFN-γ increased TG2 expression in OPCs and prolonged expression of endogenous TG2 upon differentiation. However, despite the increased TG2 levels, OPC maturation was not accelerated, indicating that TG2-mediated OPC differentiation may be counteracted by other pathways. Together, our data show that TG2, either endogenously expressed, or exogenously supplied to OPCs, accelerates early OPC differentiation. A better understanding of the role of TG2 in the OPC differentiation process during MS is of therapeutic interest to overcome remyelination failure.